2015
DOI: 10.1617/s11527-015-0689-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resilient behavior of flexible pavement asphalt layers

Abstract: Asphalt concrete is a viscoelastic material that has a resilient behavior during cyclic loads. One of the important features for defining this behavior is resilient modulus (MR). Usually, asphalt mixture is laid down in two layers known as binder and surface layers at different depth beneath the road surface. The current test methods use only one loading pulse shape, namely, haversine that represents the shape of loading exerted to the binder layer. Thus, this paper investigates resilient behavior of asphalt m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The results agree with Khan et al (2015) [21], Shafabakhsh and Tanakizadeh, A. (2016) [22], Sarsam and Nihad (2019) [23].…”
Section: Effect Of Load Duration On Mrsupporting
confidence: 81%
See 1 more Smart Citation
“…The results agree with Khan et al (2015) [21], Shafabakhsh and Tanakizadeh, A. (2016) [22], Sarsam and Nihad (2019) [23].…”
Section: Effect Of Load Duration On Mrsupporting
confidence: 81%
“…At the high test temperature of 40 o C, the differences between Mr of the binder and surface layers were time-dependent and decreased with an increase in the loading duration. The test results revealed that the difference between resilient behavior of the binder and surface layers was more apparent at high temperatures and under fast traffic loadings, as also reported elsewhere [22]. Under different traffic loading the WMA less elasticity than that of HMA mixture as illustrated by Sarsam and Nihad (2019) [23].…”
Section: Introductionsupporting
confidence: 75%
“…The traversing knob of the planimeter can then be used for the determination of the area of the WZ from the image of the core. The percentage of WZ for a core sample was determined by [2]: An optical microscope was used to view the detailed surface structure regarding aggregate particles weak zones in asphalt mixture specimens [47][48][49][50]. The effects of change in aggregate weak zones on resilient moduli need to be recognized.…”
Section: Methodsmentioning
confidence: 99%
“…Resilient modulus (M RT ) is the key parameter for the design of asphalt pavements. Asphalt mixture is a viscoelastic material which shows resilient behavior during cyclic loadings [2]. Several factors affect the resilient modulus (M RT ) of asphalt mixture, i.e., binder grade, temperature, loading pulse duration, loading pulse shape, moisture, indirect tensile strength, aggregate geometry, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the modulus of the AC layer under 15~35°C is usually used in pavement structure design in many countries (IRC, 2012;Corté & Goux, 1996;AASHTO, 1993;Ministry of Transport of China, 2006;Austroads, 2017). Consequently, a typical constant value of 2000 MPa was defined as the modulus of the AC layer under the specified temperature range based on the previous studies reflecting on results of laboratory tests (Austroads, 2017;Brown & Foo, 1991;Fakhri & Ghanizadeh, 2014;IRC, 2012;Lavasani et al, 2015;Ministry of Transport of China, 2006;Shafabakhsh & Tanakizadeh, 2016;Venudharan & Biligiri, 2015). At the same time, the modulus of the base layer was considered as a variable ranging from 500 MPa to 6000 MPa according to the findings presented in Section 1, that is to say, R m is distributed in a range from 0.25 to 3.…”
Section: Pavement Structure and Materials Propertiesmentioning
confidence: 99%